The prevalence and predictors of feeding difficulties in children at self-feeding transition stage - Tang, Meng Yan; Liu, Xiao Mei; Yang, Fan (Frontiers in Pediatrics, 2023)
Aim: To understand the prevalence of feeding difficulties (FD) in young children at self-feeding transition stage (6-24 months age), and the protective and risk predictors associated with FD are to be determined through this study. Methods: A cross-sectional study was conducted within 5 representative Women’s and Children’s hospitals in Chengdu, Southwest China. Children age 6-24 months who underwent routine child health care examination at outpatient and their parents were enrolled, while the Montreal Children’s Hospital Feeding Scale which is validated was used to determine whether these children have FD. Results: A total of 1211 subjects were enrolled in this survey, where 380 children were reported as FD with an prevalence of 31.4%. Adjusted binary logistic regression in the multivariate analysis showed 10 independent predictors of FD. Specifically there were 6 risk predictors: 1) frequent constipation (OR=1.603, CI=1.006-2.555) in CHILD sub-theme; 2) anxiety (OR=4.322, CI=3.074-6.079) and 3) indulgent parenting style (OR=2.108, CI=1.306-3.405) in PARENT sub-theme; 4) luring to eat (OR=2.806, CI=2.000-3.937), 5) forcing to eat (OR=2.040, CI=1.407-2.958), and 6) allowing playing during mealtime (OR=2.023, CI=1.435-2.853) in FEEDING PRACTICE sub-theme. The remaining 4 factors were protective predictors including 1) food preparing (OR=0.586, CI=0.385-0.891) in FOOD sub-theme; 2) observing hunger and satiety signals (OR=0.667, CI=0.457-0.974), 3) interacting with child during mealtime (OR=0.505, CI=0.308-0.828), as well as 4) providing exclusive tableware (OR=0.370, CI=0.191-0.719) in FEEDING PRACTICE sub-theme. Conclusions: There appeared to be an increasing trend of FD prevalence. Child health care clinicians and pediatricians are expected to attach more importance to FD in their daily work, and are obliged to provide parents with practical and effective preventive strategies highlighted in this study.